The Labor Party of Belgium (PTB-PVDA): A Modern Radical Left Party? - Delwit, Pascal (Frontiers in Political Science, 2022)
In a phase of political and electoral downturn of several radical left parties, the Labour Party of Belgium (PTB-PVDA) strikes the imagination due to its increasing influence. A party of Maoist origin, the PTB-PVDA has been undergoing organizational and communication change since the mid-2000s. In this article, we argue that these changes have created a very singular party. Going against prevailing partisan developments, the heart of the party remains the party-in-central-office. The party has quite a dynamic life between elections, seeks to recruit and recruits party members, trains and mobilizes its membership, borrowing from the paths of historical Belgian pillarization or the model of party of social integration. At the same time, the PTB-PVDA incorporates current partisan modifications: a strong personification, a great investment in social networks, a populist rhetoric, a redesigned communication and a focus on elections to be able to benefit from public party funding. This combination of old and new makes it one of a kind party in Europe and among the European Radical Left. However, this original organizational scheme raises the question of its fate: the aggregation of the various elements requires that it remains in the parliamentary opposition.